MECHANICAL AND PHYSICAL PROPERTIES ANALYSIS OF HIGH DENSITY POLYETHYLENE (HDPE)/DAMMAR RESIN BLEND AS POLYMER MATRIX IN RAMIE FIBER COMPOSITE - Ahmad Ramadhan, Faiq
The use of natural fibers in composite materials is an alternative to synthetic fibers which have weaknesses in environmental problems and health hazards to humans. However, natural fibers combined with a polyolefin matrix such as HDPE have lower compatibility due to differences in polarity. This results in poor fiber-matrix interface quality and causes sub-optimal mechanical properties of composite. This research aimed to study the effect of dammar resin addition to HDPE matrix on the mechanical and physical properties of ramie fiber composite. Dammar resin was added to the HDPE material through a blending process using extrusion and then used as a matrix for the thermoplastic composite fabrication. The addition of dammar resin in various concentrations to HDPE material was evaluated towards its density according to ASTM D792, tensile strength according to ASTM D882, and melt flow rate according to ASTM D1238. In addition, the interfacial shear strength between HDPE/dammar matrix and ramie fibers was analyzed using a fiber pull-out test. The tensile strength of ramie fiber/HDPE composites was tested according to ASTM D3039 and the density was based on ASTM D792. The results showed that the addition of dammar resin to HDPE increased the density and the melt flow rate value of the polymer matrix. On the other hand, it decreased the tensile strength of the polymer matrix. The addition of dammar resin successfully enhanced the interfacial shear strength of the thermoplastic composite. In ramie fiber composites, the addition of dammar resin can increase the tensile strength and density of the composite.